Organization of the educational discipline «Pedagogical rhetoric» in university - Elena G. Protsenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper discusses the content and specifics of the discipline Pedagogical rhetoric, which is mandatory in the preparation process of future teachers. The problem of rhetorical skills level associated with training at university, active practical activities, as well as with independent work of students is actualized. The content analysis of the speech training of a future teacher is presented. The purpose of the research is a theoretical substantiation of the pedagogical conditions that contribute to the development of communication principles knowledge in the professional ethics of a teacher, communication technologies in professional interaction. The theoretical significance of the study is that its results complement the scientific understanding of the pedagogical conditions for the effective development of the necessary skills of communicative influence and interaction among students in order to form a successful communicative personality being able to communicate productive in the professional pedagogical field. The results also enrich the theory and methodology of professional education in the field of the oratory and acting skills development of future teachers. Theoretical and methodological basis of the research is personal, individual, culturological, activity, psychodramatic approaches. The experience of teaching the discipline Pedagogical rhetoric at Sevastopol State University is reflected. The features of the organization of classes, the implementation of practical tasks by students, the variety of forms, methods and teaching aids used are presented. The paper emphasizes the importance of providing conditions for the creative activity of future teachers.